Share Price Reactions to Tariﬀ Imposition Announcements in the Trump Era – an Event Study of the Trade Conﬂict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariﬀ imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariﬀ announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariﬀ announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariﬀ impositions, e.g. a decrease in the companies’ future cash ﬂows and a threat of retaliation. The negative wealth eﬀects are observed irrespective of whether the Trump administration announces safeguard tariﬀs to protect domestic ﬁrms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we ﬁnd that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariﬀ, trade and ﬁrm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariﬀs; trade conﬂict

Share price reactions to tariff imposition announcements in the Trump era - An event study of the trade conflict - Wengerek, Sascha Tobias
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict

Share price reactions to tariff imposition announcements in the Trump era – An event study of the trade conflict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict

An Economic Theory of 'Destabilization War' - Gries, Thomas; Haake, Claus-Jochen
While Islamic State is the most present example, it is a fact that in many places around the globe, throughout history initially small groups have tried to challenge and destabilize or even overthrow governments by means of terrorist and guerrilla strategies. Therefore, we answer two questions. Why does a small group of insurgents believe it can overthrow the government by turning violent, even if the government is clearly superior? And how does a conflict develop into terrorism, a guerilla war, or a major conventional civil war, or is resolved peacefully? We develop a formal model for rebels and government and derive optimal choices. Further, we focus on three elements as important ingredients of a "destabilization war". All three of these - large random events, time preference (which we relate to ideology), and choice of duration of fight - are rarely considered in formal conflict theory. We can answer the above two questions using game theory analysis. First, insurgents rise up because they hope to destabilize through permanent challenging attacks. In this context, large randomness is an important ally of rebels. While each individual attack may have a low impact, at some point a large random event could lead to success. Hence, the duration of activities is a constitutive element of this kind of armed conflict. Patience (low time preference), which may reflect rebels' degree of ideological motivation, is crucial. Second, the mode of warfare or the conflict resolutions that develop are generally path-dependent and conditioned on the full set of options (including compromise). Various conditions (level of funding, ease of recruitment, access to weapons) influence different modes of warfare or a peaceful compromise in a complex way.
Keywords: terrorism; civil war; conflict duration; game theory; stochastic process; ideology

My Mother: My Best Friend? Adults’ Relationships with Significant Others Across the Lifespan - Buhl, Heike M. (Journal of Adult Development)
In order to investigate the significance of adults’ relationship to their parents, this relationship is compared to relationships with siblings, friends, partners, and children. German adults (N = 902) between the ages of 20 and 86 completed the Network of Relationships Inventory (Furman and Buhrmester 1992). Participants felt most supported by their partners, followed by their children, mothers, friends, fathers, and siblings. Conflicts were more frequently found within the family (especially with the partner, followed by children, mothers, fathers, and siblings) than with friends. Except for partner relationships, both conflict and support decreased with age. Concerning relative power within their relationships, partners, mothers, and siblings are seen as equals, friends and especially fathers are perceived as more powerful, and children as less, yet increasingly powerful. Regarding all relationship types and relationship qualities, the differences between women and men were small.
Keywords: Family; Friends; Support; Conflict; Power